Optimization and Impact Analysis of PV Penetration in Radial Distribution System: A Case Study of Panbari Feeder - Bhusal, Hari; Parajuli , Amrit; Khadka, Srijan; Sah, Radhika Kumari; Jha, Shailendra Kumar (Journal of Electronics and Electrical Engineering, 2025)
The integration of distributed generation is one of the most effective alternative methods for enhancing the voltage profile and reducing power loss in radial distribution systems (RDS). This study investigates the impact of integrating photovoltaic (PV) generation on distribution systems, considering radial distribution networks. The IEEE 33 bus RDS and Panbari Feeder of the Dharan Substation are selected as candidate systems. Particle swarm optimization (PSO) and genetic algorithm (GA) are proposed for determining the optimal location and sizing of single and multiple PV installations, considering minimum power loss as the objective function. The results are analyzed in terms of voltage profile improvement and power loss minimization with PV integration. Additionally, a comparative analysis is conducted for the system with PV integration and PV with capacitor bank for reactive power injection. An economic analysis is performed to determine the optimal number of distributed generator (DG) integrations. Through sensitivity analysis, the most sensitive buses are identified, and power-voltage (P-V) curves are plotted for these buses in the base case and cases after integration of PV only and PV with capacitor banks. The results are examined and compared in terms of load margin limit and critical voltage point. Among single and multiple PV integrations, the integration of two PV installations is found to be most suitable based on economic analysis. Simulation results demonstrate that the integration of PV sources in existing RDS has a positive impact on steady-state voltage stability. Furthermore, improvements in voltage profile and significant reductions in system power loss are observed.